Inulinase immobilisation in PAA/PEG composite for efficient fructooligosaccharides production - Temkov, Mishela; Dimitrovski, Darko; Velickova, Elena; Krastanov, Albert (Informa UK Limited, 2020)
Inulinase was immobilised by entrapment method in polyacrylamide/polyethylene glycol composite and evaluated for its efficiency for short-chain fructooligosaccharides (3–6 degrees of polymerisation) production in batch hydrolysis system. Aqueous two-phase polymerisation technique was used to synthesise the composite, where aqueous polyethylene glycol 1000 containing the enzyme was used as dispersant with ammonium persulfate as initiator. The characteristics of free and immobilised inulinase were investigated and compared, and the results showed shift of pH and temperature optimum and change in stability caused by the immobilisation material. The immobilised preparation retained 50% of its initial activity after 20 successive batch cycles of 1 h each. The conversion degree of highly polymerised inulin to fructooligosaccharides (3–6 degrees of polymerisation) was 36% when using 30% PAA/PEG, w/v.